COMBINATIONAL FYM AMENDMENT EFFECT IN PADDY SOIL - G.Selvalakshmi , F.Jeyamangalam, M.Nagarajan (Chelonian Research Foundation, 2024)
Adding organic amendments to the soil improves soil physical structures alertly, it rejuvenates soil from ill effect and builds- up a positive effect on growth parameters, crop production which equalizes the yield similarities as like as CF’S input without harming the agro-ecological chain. The main objective is to reduce the physical constraints of the soil to supply right fertilizer dosage level as nutrient input so that sustained organic farming vibrantly attracts furthermore for large scale application. Present paper deals with TKM-9 (Paddy variety) cultivation under Randomized Block Design (RBD) having 13 treatments with three replication. Organic compost mannure (FYM, VC and VWC) with different dosage additively with different combination levels are supplied to each plots except control plot (no mannure). From soil samples test data like soil pH, N, P,K their inter relational effects is compared with control plot Viz its significance difference of N,P,K values are statistically analyzed using SPSS software version 26.